Kidney Normothermic Machine Perfusion Can Be Used as a Preservation Technique and a Model of Reperfusion to Deliver Novel Therapies and Assess Inflammation and Immune Activation - Mellati, Azita; Lo Faro, Letizia; Dumbill, Richard; Meertens, Pommelien; Rozenberg, Kaithlyn; Shaheed, Sadr; Snashall, Corinna; McGivern, Hannah; Ploeg, Rutger; Hunter, James (Frontiers in Immunology, 2022)
Ischaemia-reperfusion injury (IRI) is an inevitable process in transplantation and results in inflammation and immune system activation. Alpha-1 antitrypsin (AAT) has anti-inflammatory properties. Normothermic Machine Perfusion (NMP) can be used to deliver therapies and may help in assessing the effects of IRI and immunity. This study investigated the effects of AAT on IRI and inflammation in pig kidneys when administered during preservation, followed by Normothermic Reperfusion (NR) with autologous whole blood, as a surrogate for transplant. Two different models were used to deliver AAT or placebo to slaughterhouse paired pig kidneys. Model 1: 7h Static cold Storage (SCS) + 3h NR (n=5 pairs), where either AAT (10mg/mL) or placebo were delivered in the flush following retrieval. Model 2: 4h SCS + 3h NMP + 3h NR (n=5 pairs), where either AAT or placebo were delivered during NMP. Injury markers and cytokines levels were analysed in perfusate, and HSP-70 was analysed in biopsies. AAT delivered to kidneys showed no adverse effects on perfusion parameters. HSP-70 fold changes were significantly lower in AAT group during NMP (P<0.01, Paired t-test), but not during NR. IL-1ra fold changes were significantly higher in AAT group during NR model 1 (P<0.05, two-way ANOVA). In contrast to AAT group, significant upregulation of IL-1β and IL-6 between t=90min vs t=180min and IL-8 between baseline vs t=90min were observed in control group in NR model 2 (p<0.05, Tukey's multiple comparisons test). However, overall inflammatory cytokines and injury markers showed similar levels between groups. Delivery of AAT to pig kidneys was safe without any detrimental effects. NMP and NR provided excellent methods for comparison of inflammation and immune activation in the delivery of a novel therapy.